2011
DOI: 10.1007/s11090-011-9313-4
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Nanoparticles Formation from Solution Plasma Using Edge-Shielded Electrode

Abstract: Abstract. Because of the easy massproduction, synthesis of metallic nanoparticles from a solution plasma is an attractive method. However, a solution plasma produces a highly inhomogeneous electric field via transition to full-plasma, and the products are partially oxidized and agglomerated, with a wide size-distribution. Here, we show a simple method of suppressing oxidation of products. An electrode tip was shield by a glass tube and a voltage of up to 180 V was applied with the electrolyte of 0.1 M NaOH sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In this solution plasma technique [19][20] , an electrode was used as the raw material for the preparation of nanocrystals. Various nanoparticles such as Ni 19,20 , Au 20,21 , ZnO 22 have been synthesized via solution plasma. In general, the solution plasma technique offers many advantages, such as (1) simple experimental setup, (2) no requirement for gas supply, (3) higher productivity than conventional solution processes, and (4) applicability to mass production.…”
Section: Introductionmentioning
confidence: 99%
“…As reported previously, 16,19,22,23 the experimental setup consisted of two electrodes in a glass cell with a capacity of 300 ml. The cathode consisted of a metal wire with a diameter of 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…14,15 Recently, a solution plasma has been applied to the synthesis of nanoparticles. The produced particle size and compositions were affected by the plasma conditions, such as the electrode shape, 16,17 voltage, 18,19 atmospheric pressure, 20 and material. 21 Previous reports indicated that the shape of the electrode affects the plasma conditions and obtained nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation